Modeling for neurosurgical laser interstitial thermal therapy with and without intracranial recording electrodes - Daniel W. Keefe; David T. Christianson; Greyson W. Davis; Hiroyuki Oya; Matthew A. Howard, III; Christopher I. Petkov; Fatima Toor (Current Research in Neurobiology)
Laser thermal ablation has become a prominent neurosurgical treatment approach, but in epilepsy patients it cannot currently be safely implemented with intracranial recording electrodes that are used to study interictal or epileptiform activity. There is a pressing need for computational models of laser interstitial thermal therapy (LITT) with and without intracranial electrodes to enhance the efficacy and safety of optical neurotherapies. In this paper, we aimed to build a biophysical bioheat and ray optics model to study the effects of laser heating in the brain, with and without intracranial electrodes in the vicinity of the ablation zone during the LITT procedure. COMSOL Multiphysics finite element method (FEM) solver software was used to create a bioheat thermal model of brain tissue, with and without blood flow incorporation via Penne's model, to model neural tissue response to laser heating. We report that the close placement of intracranial electrodes can increase the maximum temperature of the brain tissue volume as well as impact the necrosis region volume if the electrodes are placed too closely to the laser coupled diffuse fiber tip. The model shows that an electrode displacement of 4 mm could be considered a safe distance of intracranial electrode placement away from the LITT probe treatment area. This work, for the first time, models the impact of intracranially implanted recording electrodes during LITT, which could improve the understanding of the LITT treatment procedure on the brain's neural networks a sufficient safe distance to the implanted intracranial recording electrodes. We recommend modeling safe distances for placing the electrodes with respect to the infrared laser coupled diffuse fiber tip.